ANALYSIS OF PREFERRED FREIGHT FORWARDING SERVICE USING ANALYTICAL HIERARCHY PROCESS METHOD - Surya Kelana Saputra; Anggi Oktaviani; Dahlia Sarkawi; Deny Novianti (Jurnal Riset Informatika, 2022)
Buyers and sellers who use online transactions for shipping can use two face-to-face shipping methods or delivery services. Everyone needs fast and safe shipping to ensure goods are transported at the right time and place. The interest in dispatch administrations is progressively required. The ongoing portability constraints are compelling many people to purchase online instead of shopping centers. The Analytical Hierarchy Process technique was created in the mid-1970s by Dr. Thomas L. Saaty, a mathematician from the University of Pittsburgh. The Analytical Hierarchy Process is designed to rationally capture people's perceptions closely related to specific problems through procedures designed to arrive at a preference scale among various sets of alternatives. This choice model decays a complex multi-rules issue into a solitary various, leveled structure. From the study results, it can be concluded that J&T has the highest score of 0.345 (34.5%), then JNE with a score of 0.339 (33.9%), SICEPAT with a score of 0.316 (31.6%), so that the most desirable Expedition Service based on data processed from 103 respondents is J&T.